2015
DOI: 10.1111/jerd.12170
|View full text |Cite
|
Sign up to set email alerts
|

Modified Tunnel Technique Combined with Enamel Matrix Derivative: A Minimally Invasive Treatment for Single or Multiple Class I Recession Defects

Abstract: This modified tunnel technique using enamel matrix derivative potentially represents a clinically and esthetically satisfactory treatment of Miller Class I recession defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
0
14
0
3
Order By: Relevance
“…Search results based on the PRISMA guidelines are depicted in Figure . Twenty articles reporting on 1181 recessions treated with TUN, with a mean follow‐up of 11 months, were included in the present systematic review (Tables and ) . Among these, six RCTs comparing CAF to TUN were considered for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Search results based on the PRISMA guidelines are depicted in Figure . Twenty articles reporting on 1181 recessions treated with TUN, with a mean follow‐up of 11 months, were included in the present systematic review (Tables and ) . Among these, six RCTs comparing CAF to TUN were considered for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles focused on localized GR defects, three treated both single and multiple GR defects, and the remaining studies included only multiple GR defects . One article treated only Miller Class III GRs; three studies, Miller Class I, II, and III GR defects; and the remaining articles focused only on Miller Classes I and II GR defects . The general characteristics of the included studies are outlined in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of CPF and EMD provided a comparable percent root coverage to that of CPF alone (75% for EMD and 71% for CPF alone) [39], and CPF + SCTG (89% for EMD and 93% for SCTG) [25], but a less promising outcome than tunnel technique with SCTG (72% for EMD and 98% for SCTG) [28], as discussed in previous paragraphs. In their case series report, Vincent-Bugnas et al evaluated the clinical results of the combination of tunnel technique and EMD in single and multiple gingival recession defects [50]. The results calculated from patients with multiple defects indicated that this procedure yielded mean root coverage of 92% at 24 months.…”
Section: Enamel Matrix Derivativementioning
confidence: 97%
“…A total of four studies reported the clinical effectiveness of enamel matrix derivative (EMD) on multiple gingival recession defects, with mean percent root coverage ranging from 72 to 92% [25,28,39,50]. Comparison of EMD to another treatment procedure was made in three out of four studies.…”
Section: Enamel Matrix Derivativementioning
confidence: 99%